A Quality Initiative: A System-Wide Reduction in Serious Medication Events Through Targeted Simulation Training. Issue 5 (October 2018) - Hebbar, Kiran B.; Colman, Nora; Williams, Lorisa; Pina, Jessica; Davis, Lisa; Bost, James E.; Jones, Halli; Frank, Gary
Abstract : Introduction: Medication administration events (MAEs) are a great concern to the healthcare industry, because they are both common and costly. Pediatric patients pose unique challenges to healthcare systems, particularly regarding the safety of medication administration. Our objectives were to improve adherence to best practices, decrease MAEs, and decrease cost related to error reduction rates by implementing a scenario-based simulation training program for frontline nursing staff in the general care units, emergency departments, and intensive care units within our institution. Methods: Children's simulation center in conjunction with the medication safety workgroup developed a 2-hour target-specific simulation-based training. This quality initiative focused on implementation of a MAE bundle that included the following three elements: The Five Rights, MedZone, and Independent Double Check. Adherence to the use of bundle elements was monitored via bedside auditing for 18 months after the intervention. This audit was accomplished using an institution-wide MAE reporting system. The 2012 Healthcare Cost and Utilization Project Kids' Inpatient Database and 2014 Children's Hospital Association, Pediatric Health Information System databases were used to estimate cost impact. Results: A total of 1434 nurses from our intensive care units, emergency departments, and general care inpatient units participated in simulation training. Nursing adherence to the MAE bundle in the 18-month period after simulation increased by 33%, from January 2014 to June 2015. Medication administration event monitoring during the preintervention, intervention, and postintervention periods demonstrated a decrease in error rate from 2.5 events per month to 0.86 events per month This error reduction correlated to an estimated charge savings of 165, 000 to 255, 000 and a cost impact of 90, 000 to 130, 000 per year. Conclusions: Target-specific simulation-based training on a large scale has improved adherence with best practice guidelines and has led to a significant reduction in MAEs.